A dual‐port dual‐frequency integration antenna design. Issue 12 (23rd July 2020) - Tang, Zhiyi; Yang, Duo; Ma, Chao; Wei, Lusong; Zhang, Bin; Huangfu, Jiangtao
Abstract: In this article, a compact dual‐port dual‐frequency slot antenna compatible with printed circuit board (PCB) technology is proposed. The antenna has two feed structures for two frequencies with slots and the capacitive matching circuits. The antenna radiates at specific frequency with the matching network and the frequency of the antenna can be adjustable by changing the matching element parameters. Taking the advantage of resonance by the subwavelength feed slots, the efficient radiation can be achieved at the outer ground edge of the PCB board, thus contributing to the excellent performance of gain and the good isolation between two frequency band paths. In consideration given to the wireless communication application bands, the antenna is designed to work at 1.57 and 2.4 GHz. The experimental radiation patterns show a unidirectional antenna with maximum radiation of 0.86 dBi in 171° direction at 1.57 GHz and maximum radiation of 5.2 dBi in 278° direction at 2.4 GHz, respectively. The proposed compact cost‐effective antenna demonstrates the potential of application in small multifrequency Internet of Things devices to drive WiFi, Bluetooth, and GPS.